pXRF Skeletal Measurements as an Assessment Tool for Environmental Exposure to Lajes Field–Derived Contaminants (Terceira Island, Azores, Portugal): pXRF Skeletal Measurements as an Assessment Tool for Environmental Exposure to Lajes Field–Derived Contaminants (Terceira island, Azores, Portugal) - Rodrigues, Félix; Rodrigues, António Félix; Matos, Vítor; Mendes, Armando; Ferreira, Maria Teresa (Biological trace element research, 2025)
Lajes Field is an Atlantic Portuguese military air base that has been used by the USA since the Cold War, primarily for intercontinental refueling. For this purpose, large fuel tanks and an extensive pipeline network were constructed within the municipality of Praia da Vitória, on Terceira Island, Azores. Over the past two decades, fuel leaks were detected and confirmed to have contaminated soils and the aquifers that supply water for public use. For the latter, identified contaminants include TPH, PAH, BTEX, VOCs, and metals. Although risk assessment reports have identified unacceptable risks to human health, and journalistic investigations suggest unusually high cancer rates, no assessment on possible human exposure has been conducted to date. To address this gap, metals, serving as a proxy for overall contamination exposure, were measured using portable X-ray fluorescence (pXRF) in the First Identified Skeletal Collection of the Azores (CEI/Açores). A total of 64 skeletons with known places of last residence were selected (44 from Angra do Heroísmo, where no exposure risk is present, and 20 from Praia da Vitória, where risk is present). No significant differences in mean ages at death were observed between the groups, and sex distribution was similar. Additionally, soil samples from 46 graves were analyzed to assess potential diagenesis. Greater concentrations of Sb, As, Cd, Cr, Au, Mo, Sr, Sn, U, and Zr were found in individuals from Praia da Vitória ( p < 0.05). Soil measurements, Pearson’s correlation test, and a principal component analysis suggest that the differences in Zr and As levels can be partially attributed to diagenesis. For the remaining metals, the observed differences likely result from other factors, including potential contamination exposure, particularly for Cd, Cr, and Mo. Although this pioneering study contributes to the ongoing discussion on the subject, further research should be conducted both in the CEI/Açores and the living population to further discuss this issue.